An integrated functional and clinical genomics approach reveals genes driving aggressive metastatic prostate cancer - Rajdeep Das (Nature Portfolio, 2021)
It is hypothesized that there are a number of tumor specific driver genes for metastatic prostate cancer. Here, the authors perform genome-wide CRISPRi screens and integrate these data with metastatic prostate cancer functional and clinical genomics data to show that KIF4A and WDR62 drive aggressive prostate cancer phenotypes.